Transcranial magnetic stimulation in neurosurgery - A. Yu. Dmitriev; V. G. Dashyan (Неотложная медицинская помощь)
Transcranial magnetic stimulation (TMS) is a relatively new diagnostic and therapeutic method. Its widespread introduction into neurosurgical practice began in 2009. The method is used for non-invasive detection of eloquent brain areas. The combination with tractography facilitates the projection of pathways. The review summarizes the main results of TMS in the planning of neurosurgical interventions. We described the principle of method, analyzed its beneﬁ ts and shortcomings, compared it with direct cortical stimulation which is a “gold standart” in detection of eloquent brain centers.